Icthyofaunal diversity of upper stretches of the River Brahmaputra in Jorhat district of Assam - Hrishikesh Kashyap Bezbaruah; Mogalekar H.S; Sachin W. Belsare; Satyajit Belsare; Sandeep B. Gore; Sonal R. Kalbande (Journal of Indian Fisheries Association, 2023)
The study was conducted from April 2022 to September 2022 to explore the icthyofaunal diversity of Brahmaputra River in Jorhat district of Assam. The present fish faunal record revealed presence of 23 species of fish belonging to 17 genera, nine families and six orders. Cyprinidae was dominant family with seven species in the study area. In terms of species distribution catfishes are dominant with 10 species in the category. Of the 23 species recorded, two species are categorized under near threatened category and one under vulnerable category. This report could be useful for conservation and management of fishes in Jorhat district of Assam.